Decarboxylative Peptide Macrocyclization through Photoredox Catalysis. (17th November 2016) - McCarver, Stefan J.; Qiao, Jennifer X.; Carpenter, Joseph; Borzilleri, Robert M.; Poss, Michael A.; Eastgate, Martin D.; Miller, Michael M.; MacMillan, David W. C.
Abstract: A method for the decarboxylative macrocyclization of peptides bearing N‐terminal Michael acceptors has been developed. This synthetic method enables the efficient synthesis of cyclic peptides containing γ‐amino acids and is tolerant of functionalities present in both natural and non‐proteinogenic amino acids. Linear precursors ranging from 3 to 15 amino acids cyclize effectively under this photoredox method. To demonstrate the preparative utility of this method in the context of bioactive molecules, we synthesized COR‐005, a somatostatin analogue that is currently in clinical trials. Abstract : Im großen Kreis : Eine decarboxylierende Makrocyclisierung von Peptiden, die N‐terminale Michael‐Akzeptoren tragen, unter Photoredoxkatalyse ermöglicht die Synthese cyclischer Peptide, die γ‐Aminosäuren enthalten, und ist mit Funktionalitäten natürlicher Aminosäuren verträglich. Lineare Vorstufen aus 3 bis 15 Aminosäuren werden effizient cyclisiert.